2018
DOI: 10.1021/acsami.7b17112
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Resonance Coupling in Single Si Nanoparticle–Monolayer WS2 Structures

Abstract: Two-dimensional semiconducting transition metal dichalcogenides (TMDCs) are extremely attractive materials for optoelectronic applications in the visible and near-infrared range. Coupling these materials to optical nanocavities enables advanced quantum optics and nanophotonic devices. Here, we address the issue of resonance coupling in hybrid exciton-polariton structures based on single Si nanoparticles (NPs) coupled to monolayer (1L)-WS. We predict a strong coupling regime with a Rabi splitting energy exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
127
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 69 publications
7
127
1
Order By: Relevance
“…These hybrid states have attracted considerable attention recently as they are of interest for quantum and nonlinear optics applications, as well as for modification of photochemical reactions [46][47][48][49] . Mie resonances of Si and perovskite nanostructures, as well as WS 2 nanotubes, were recently shown to hybridize within various excitonic systems [50][51][52][53][54] . Here we observe hybridization of anapoles and excitons within a single WS 2 nanodisk.…”
Section: Resultsmentioning
confidence: 99%
“…These hybrid states have attracted considerable attention recently as they are of interest for quantum and nonlinear optics applications, as well as for modification of photochemical reactions [46][47][48][49] . Mie resonances of Si and perovskite nanostructures, as well as WS 2 nanotubes, were recently shown to hybridize within various excitonic systems [50][51][52][53][54] . Here we observe hybridization of anapoles and excitons within a single WS 2 nanodisk.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, fewer degrees of freedom can be offered by two-dimensional materials, whose homogeneity and in-plane dipole orientation might result in a simpler system to be studied. [43,54] III. CONCLUSIONS…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we consider c-Si for the particle material, because of its large refractive index in the visible range and moderate losses [30]. SiNPs of spherical shape can be fabricated chemically [33] or with fs-laser ablation [34]. In [33], [32], it has been shown that spherical SiNPs and Si nanowires can be placed on 2D TMDCs (WS2 and MoS2, respectively) without damaging their crystalline structure, where an additional thin layer of h-BN can be used for protection or isolation of 2D TNDCs [35].…”
Section: Resultsmentioning
confidence: 99%